2012
DOI: 10.1200/jco.2011.37.9511
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Financial Hardship in Patients Receiving Adjuvant Chemotherapy for Colon Cancer: A Population-Based Exploratory Analysis

Abstract: PurposeCharacteristics that predispose patients to financial hardship during cancer treatment are poorly understood. We therefore conducted a population-based exploratory analysis of potential factors associated with financial hardship and treatment nonadherence during and following adjuvant chemotherapy for colon cancer.Patients and MethodsPatients diagnosed with stage III colon cancer between 2008 and 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
261
4
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(294 citation statements)
references
References 15 publications
24
261
4
2
Order By: Relevance
“…Compared with non-CCEP participants, those enrolled in the CCEP were younger and had lower incomes. Studies have shown that, in general, younger patients and those with lower incomes experience considerable cancer-related financial problems [24,[48][49][50][51]. We also found that a higher proportion of CCEP participants were enrolled in phase I clinical trials and had metastatic disease.…”
Section: Discussionsupporting
confidence: 56%
“…Compared with non-CCEP participants, those enrolled in the CCEP were younger and had lower incomes. Studies have shown that, in general, younger patients and those with lower incomes experience considerable cancer-related financial problems [24,[48][49][50][51]. We also found that a higher proportion of CCEP participants were enrolled in phase I clinical trials and had metastatic disease.…”
Section: Discussionsupporting
confidence: 56%
“…Less than half of patients with stage III CRC discuss problems of treatment costs with their physicians. 9 Furthermore, previous studies have not evaluated the role that treatment complications may play in patients' susceptibility to economic hardship. Therefore, surgeons and other providers need to be particularly aware that patients with CRC who suffer treatmentrelated complications are at increased risk for economic hardship during treatment.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Beyond the clinical consequences, however, many patients with cancer also suffer significant economic hardship from their disease and its treatment. [8][9][10][11] Even among those with medical insurance, cancer therapies may require substantial out-of-pocket expenditures for medications, copayments for diagnostic testing, hospital and outpatient care, travel, and home care. [10][11][12][13] The financial impact of cancer can result in significant emotional and family stress and may impair overall quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…The very high cost of these new targeted agents, however, means that high co-payments can effectively exclude access to the drug from large segments of the population. To the extent that even modest co-pays can lead to substantial out-of-pocket costs, several studies now suggest that financial distress and bankruptcy are increasingly common problems for cancer patients and their families [25][26][27].…”
Section: Coverage Decisions For New Therapies For Mrccmentioning
confidence: 99%